ANALISIS PENGARUH ELEMEN VISUAL TERHADAP PREFERENSI KONSUMEN DALAM PEMILIHAN PRODUK PADA PLATFORM SHOPEE - Muhammad Zia Ulhaq; Andi Fauziyah Hijrina Fatimah (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2026)
The rapid expansion of e-commerce has fundamentally reshaped consumer–product interactions, shifting reliance toward digitally mediated visual representations. This study investigates the impact of visual elements on consumer product selection decisions on the Shopee platform. Employing a quantitative survey design, data were collected from 210 active users in Indonesia and analyzed using multiple linear regression. The findings reveal that image quality and color exert significant positive effects on purchase decision-making, whereas typography and layout do not demonstrate significant individual influences. Nonetheless, all visual elements collectively exhibit a significant effect, explaining 62% of the variance in consumer decisions. These results indicate that consumers prioritize visually salient and emotionally engaging cues over supporting visual attributes when evaluating products in online environments. From a theoretical perspective, this study extends the applicability of the Stimulus–Organism–Response (S-O-R) framework and the Technology Acceptance Model (TAM) by demonstrating how visual stimuli shape cognitive evaluations and behavioral outcomes in digital commerce contexts. Practically, the study underscores the strategic importance of optimizing product visuals—particularly image quality and color—to enhance consumer engagement and drive purchase decisions. Keywords: Visual Communication Design; E-Commerce; Consumer Decision-Making; Visual Perception; Online Shopping Behavior